Recombinant tissue plasminogen activator injected into the vitreous cavity may penetrate the retinal veins of a porcine model of vascular occlusion. Issue 7 (15th March 2006) - Mahmoud, T H; Peng, Y-W; Proia, A D; Davidson, M; Deramo, V A; Fekrat, S
Abstract : Aim: To determine if recombinant tissue plasminogen activator (rtPA) injected into the vitreous cavity can penetrate the retinal vessels of porcine eyes with or without vascular occlusion. Methods: Eight eyes (group I) of four pigs underwent clamping of the optic nerve flush with the globe for 90 minutes. One hour after reperfusion, one eye of each pig was injected with 75 μg of rtPA, and the fellow eye was injected with balanced salt solution (BSS). Eyes were processed for immunohistochemistry. Four additional eyes (group II) of two pigs were subjected to the same injections, but without optic nerve clamping. Results: After reperfusion, the clinical picture was similar to that of a central retinal vein occlusion. Immunoperoxidase staining showed rtPA only in the retinal veins but not the retinal arteries in all eyes injected with rtPA in both groups I and II. Those eyes also showed intense rtPA staining at the level of the internal limiting membrane (ILM). No staining was seen at the level of the ILM or inside the retinal vessels in the BSS injected eyes. Immunofluorescence staining showed intense staining at the level of the ILM, but not inside the retinal vessels in the rtPA-injected eyes. Conclusions: rtPA may penetrate the retinal veins, but not the arteries of porcine eyes with and without vascular occlusion. The ILM may play a part in preventing rtPA penetration.